KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMPN 4 PEKANBARU - Putrianis Putrianis; Auzar Auzar; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is titled The Ability to Write the Descriptive Text the Students of Class VII of 4 Junior High School Pekanbaru. This study aims to describe the ability to write the descriptive text of students of class VII of 4 Junior High School Pekanbaru, to describe the different ability to write the descriptive text of the students of class VII of 4 Junior High School Pekanbaru between groups and samples. This study data is in the from of test result from the ability to write the descriptive text of the students of class VII of 4 Junior High School Pekanbaru which consisting of nine classes with population of 216 students and the sample numberis 140 students. The technique of data collection is by giving a test to the students by writing the descriptive text. To find out how high the ability to write the descriptive text of the students of class VII of 4 Junior High School Pekanbaru is calculated using the wilcoxon test. To now whether there is a mean difference between the sample groups is calculated using kruskall-wallis. Based on the study, it is obtained that 1. The ability to write the descriptive text is low. 2. The difference in the ability to write descriptive text between the sample groups is the same. It means that there is no difference in the ability to write descriptive text between the sample groups.Keywords: Ability, Writing, Text, Description